Beneficial effects of treadmill training in experimental diabetic nerve regeneration - Tais Malysz; Jocemar Ilha; Patrícia Severo do Nascimento; Katia De Angelis; Beatriz D'Agord Schaan; Matilde Achaval (Clinics, 2010)
OBJECTIVES: We investigated the effects of treadmill training (10 weeks) on hindlimb motor function and nerve morphometric parameters in diabetic rats submitted to sciatic nerve crush. MATERIALS AND METHOD: Wistar rats (n = 64) were divided into the following groups: non-diabetic; trained non-diabetic; non-diabetic with sciatic nerve crush; trained non-diabetic with sciatic nerve crush; diabetic; trained diabetic; diabetic with sciatic nerve crush or trained diabetic with sciatic nerve crush. Diabetes was induced by streptozotocin injection (50 mg/kg, iv). Hindlimb motor function was evaluated weekly by assessing sciatic functional indices, and the proximal and distal portions of the sciatic nerve were used for morphometric analysis. RESULTS: At 13 weeks post-injury, the distal nerve portion of all injured groups and the proximal nerve portion of the diabetic with sciatic nerve crush group presented altered morphometric parameters such as decreased myelinated fiber diameter (~7.4 + 0.3μm vs ~4.8 + 0.2μm), axonal diameter (~5 + 0.2μm vs ~3.5 + 0.1μm) and myelin sheath thickness (~1.2 + 0.07μm vs ~0.65 + 0.07μm) and an increase in the percentage of area occupied by endoneurium (~28 + 3% vs ~60 + 3%). In addition, in the non-diabetic with sciatic nerve crush group the proximal nerve portion showed a decreased myelinated fiber diameter (7.4+0.3μm vs 5.8 + 0.3μm) and myelin sheath thickness (1.29 + 0.08μm vs 0.92 + 0.08μm). The non-diabetic with sciatic nerve crush, trained non-diabetic with sciatic nerve crush, diabetic with sciatic nerve crush and trained diabetic with sciatic nerve crush groups showed normal sciatic functional index from the 4th,4th,9th and 7th week post-injury, respectively. Morphometric alterations in the proximal nerve portion of the diabetic with sciatic nerve crush and non-diabetic with sciatic nerve crush groups were either prevented or reverted to values similar to the non-diabetic group by treadmill training. CONCLUSION: Diabetic condition promoted delay in sciatic nerve regeneration. Treadmill training is able to accelerate hindlimb motor function recovery in diabetic injured rats and prevent or revert morphometric alterations in proximal nerve portions in non-diabetic and diabetic injured rats.